Effect of Work Facilities, Interpersonal Communication and Work Discipline on Employee Performance at PT. Pandji Waringin Malimping Lebak-Banten - Dede Ridho Firdaus (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze the effect of work facilities, interpersonal communication and work discipline on employee performance at PT. Pandji Waringin Malimping Lebak-Banten. In this study there are four variables, namely Work Facilities (X1), Interpersonal Communication (X2), Work Discipline (X3), and Employee Performance (Y). This study involved all employees of PT. Pandji Waringin Malimping Lebak-Banten as a sample is 80 employees. To get accurate results in this study using interviews, observations, and questionnaires. This research uses descriptive methods, verification analysis, inner and outer models as well as hypothesis testing and the direct influence of anther construct variables. The results of this study indicate that: (1) Work facilities have a positive and insignificant effect on employee performance. (2) interpersonal communication has a positive and significant effect on employee performance. (3) Work Discipline has a positive and significant effect on Employee Performance